2007
DOI: 10.1016/j.febslet.2007.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiolic‐acid synthase, the chemotype‐determining enzyme in the fiber‐type Cannabis sativa

Abstract: Cannabidiolic-acid (CBDA) synthase is the enzyme that catalyzes oxidative cyclization of cannabigerolic-acid into CBDA, the dominant cannabinoid constituent of the fiber-type Cannabis sativa. We cloned a novel cDNA encoding CBDA synthase by reverse transcription and polymerase chain reactions with degenerate and gene-specific primers. Biochemical characterization of the recombinant enzyme demonstrated that CBDA synthase is a covalently flavinylated oxidase. The structural and functional properties of CBDA synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
220
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(238 citation statements)
references
References 30 publications
6
220
0
2
Order By: Relevance
“…CBDA), and CBG total (= CBG ? CBGA) (Swift et al 2013;Taura et al 2007a) between sample replicates were typically \5 % RSD. One way analysis of variance (ANOVA) calculated using GenStat 64-bit Release 16.1 (VSN International 2014) indicated that there was no significant difference in THC total F 1, 130 = 0.01, P = 0.936, CBD total F 1, 130 = 0.00, P = 0.985, and CBG total F 1, 122 = 0.02, P = 0.898 between replicates.…”
Section: Linearity and Reproducibilitymentioning
confidence: 99%
See 4 more Smart Citations
“…CBDA), and CBG total (= CBG ? CBGA) (Swift et al 2013;Taura et al 2007a) between sample replicates were typically \5 % RSD. One way analysis of variance (ANOVA) calculated using GenStat 64-bit Release 16.1 (VSN International 2014) indicated that there was no significant difference in THC total F 1, 130 = 0.01, P = 0.936, CBD total F 1, 130 = 0.00, P = 0.985, and CBG total F 1, 122 = 0.02, P = 0.898 between replicates.…”
Section: Linearity and Reproducibilitymentioning
confidence: 99%
“…In a single (B) locus model, chemotype II individuals are assumed to be heterozygote for the codominant B T (THCAS) and B D (CBDAS) alleles (De Meijer et al 2003). These alleles encode functional sequence variants of THCA and CBDA synthase, and therefore the efficiency (Pacifico et al 2006) with which CBG(V)A is converted to THC(V)A (B T ) and CBD(V)A (B D ) (Sirikantaramas et al 2004;Taura et al 2007b) (Fig. 1).…”
Section: Chemotype II Variabilitymentioning
confidence: 99%
See 3 more Smart Citations